2001
DOI: 10.1046/j.1365-313x.2001.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

The tomato Rme1 locus is required for Mi‐1‐mediated resistance to root‐knot nematodes and the potato aphid

Abstract: SummaryThe tomato Mi-1 gene confers resistance against root-knot nematodes (Meloidogyne spp.) and a biotype of the potato aphid (Macrosiphum euphorbiae). Four mutagenized Mi-1/Mi-1 tomato populations were generated and screened for altered root-knot nematode resistance. Four independent mutants belonging to two phenotypic classes were isolated. One mutant was chosen for further analyzes; rme1 (for resistance to Meloidogyne) exhibited levels of infection comparable with those found on susceptible controls. Mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 47 publications
1
50
0
Order By: Relevance
“…A resistance gene against RKN, Mi-1.2, is not transcriptionally regulated but speculated to be post-transcriptionally regulated (Martinez de Ilarduya et al, 2001). Our results also supported this suggestion.…”
Section: Discussionsupporting
confidence: 84%
“…A resistance gene against RKN, Mi-1.2, is not transcriptionally regulated but speculated to be post-transcriptionally regulated (Martinez de Ilarduya et al, 2001). Our results also supported this suggestion.…”
Section: Discussionsupporting
confidence: 84%
“…The choice of growth medium for root-nematode experiments is important, as soil texture affects the severity of root infestation. Sandy loams and coarser textured soils are more conducive to infection in the field than heavy or clay soils (Sasser 1954, Raski and Johnson 1959, Thomason and Lear 1959, and researchers typically use coarse textured soils such as river bottom sand for RKN studies in the greenhouse (de Ilarduya et al 2001, Ammiraju et al 2003. However, unlike tomato, we found that Lotus roots develop poorly in sand alone, and so we tested various growth media for nematode infection.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, the occurrence of susceptibility while there is no guarding or no R gene present in the plant targeted for the Avr genes, often resulting in a disease. For example rme1, a recessive gene resistance to Meloidogyne species, which is unlinked to Mi-1 (de Ilarduya et al 2001), and compromised Mi-1-mediated resistance. Since the gene product of RME1 still unknown; the authors guessed that it may be a protein kinase performing either upstream of Mi-1 or at the initial stage of the signal transduction pathway.…”
Section: Indirect Interactionmentioning
confidence: 99%